Synergistic Effect of the MTHFR C677T and EPHX2 G860A Polymorphism on the Increased Risk of Ischemic Stroke in Chinese Type 2 Diabetic Patients - Liang Ma; Yongwei Jiang; Xiaomu Kong; Meihua Yan; Tingting Zhao; Hailing Zhao; Qian Liu; Haojun Zhang; Yongtong Cao; Ping Li (Journal of Diabetes Research, 2017)
The aim of this study was to investigate the relationship between the combined effect of MTHFR C677T (rs1801133) and EPHX2 G860A (rs751141) polymorphism and ischemic stroke in Chinese T2DM patients. This case-control study included a total of 626 Chinese T2DM patients (236 T2DM patients with ischemic stroke and 390 T2DM patients without ischemic stroke). The rs1801133 and rs751141 were genotyped using real-time polymerase chain reaction. Statistical analysis was performed with SPSS 17.0. Results showed that the combined effect of MTHFR TT and EPHX2 GG or GA + AA genotype has a higher risk of ischemic stroke compared with the control group (combined effect of MTHFR CC and EPHX2 GA + AA genotypes; OR = 3.46 and OR = 3.42, resp.; P=.001 and P=.002, resp.). The A allele showed marked association with a lower risk of ischemic stroke in patients with the lowest Hcy levels under additive, recessive, and dominant genetic models (OR = 0.45, OR = 0.11, and OR = 0.44, resp.; P=.002, P=.035, and P=.008, resp.), which was not observed in medium or high Hcy level groups. In conclusion, the T allele of rs1801133 and the G allele of rs751141 may be risk factors of ischemic stroke in the Chinese T2DM population.